2018
DOI: 10.1177/0269216318807051
|View full text |Cite
|
Sign up to set email alerts
|

Symptom prevalence and quality of life of patients with end-stage liver disease: A systematic review and meta-analysis

Abstract: Background:End-stage liver disease is a common cause of morbidity and mortality worldwide, yet little is known about its symptomatology and impact on health-related quality of life.Aim:To describe symptom prevalence and health-related quality of life of patients with end-stage liver disease to improve care.Design:Systematic review.Data sources:We searched eight electronic databases from January 1980 to June 2018 for studies investigating symptom prevalence or health-related quality of life of adult patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
188
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 202 publications
(205 citation statements)
references
References 121 publications
(228 reference statements)
10
188
1
6
Order By: Relevance
“…The physical and psychological symptom burden and social‐role consequences of ESLD are often worse than those for many non‐liver cancers. ( 4 ) The most frequently reported symptoms include pain, breathlessness, muscle cramps, sleep disturbance, fatigue, pruritus, anxiety, depression, and erectile dysfunction. ( 4 ) In addition to its direct effects on patients, ESLD is linked with a substantial caregiver emotional and physical burden, mirroring that observed in caregivers of patients with cancer.…”
Section: Organization Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical and psychological symptom burden and social‐role consequences of ESLD are often worse than those for many non‐liver cancers. ( 4 ) The most frequently reported symptoms include pain, breathlessness, muscle cramps, sleep disturbance, fatigue, pruritus, anxiety, depression, and erectile dysfunction. ( 4 ) In addition to its direct effects on patients, ESLD is linked with a substantial caregiver emotional and physical burden, mirroring that observed in caregivers of patients with cancer.…”
Section: Organization Definitionmentioning
confidence: 99%
“…( 4 ) The most frequently reported symptoms include pain, breathlessness, muscle cramps, sleep disturbance, fatigue, pruritus, anxiety, depression, and erectile dysfunction. ( 4 ) In addition to its direct effects on patients, ESLD is linked with a substantial caregiver emotional and physical burden, mirroring that observed in caregivers of patients with cancer. ( 5 ) However, interventions to improve the quality of life (QOL) for patients with ESLD and their caregivers are underdeveloped.…”
Section: Organization Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al's systematic review and meta-analysis in 2019 assessed symptom prevalence and health-related quality of life for patients with end-stage liver disease. 9 It included 80 studies from Europe, North America, Asia, and Africa and found significant physical problems including pain (30-79% patients), breathlessness (20-88%), muscle cramps (56-68%), erectile dysfunction (53-93%), sleep disturbance (26-77%), fatigue (52-86%), and pruritus (47-64%). Psychological burden was also prevalent including anxiety (14-45%) and depression (4.5-64%).…”
Section: The Tremendous Symptom Burden Of Advanced Liver Diseasementioning
confidence: 99%
“…In addition to their substantial mortality burden, it is often underappreciated that patients with advanced liver disease live with a symptom burden paralleling that of patients with advanced malignancy. 9 In an effort to improve care, the last decade has seen a surge in the number of publications addressing the palliative care needs of patients with advanced liver disease. Unlike common misperceptions, 10 palliative care is a broad umbrella term that subsumes end-of-life care.…”
mentioning
confidence: 99%